CT and MR in peritoneal malignancies: pearls and pitfalls at preoperative examination - Michela Polici; Federica Palmeri; Erica Golia; Emanuela Parri; Guido Gentiloni Silveri; Francesco Puglisi; Domenico De Santis; Marta Zerunian; Francesco Pucciarelli; Tiziano Polidori; Maria Ciolina; Paolo Sammartino; et al. (Insights into Imaging)
Abstract Peritoneal malignancies (PM) are defined as the spread of malignant epithelial cells in the peritoneal cavity. Until the recent past, the prognosis was considered extremely poor, and the treatment options had only palliative intent. Currently, new locoregional treatments have radically changed the outcome. CT is pivotal in PM diagnosis, staging, surgical planning, and determining therapeutic decisions. MRI should be evaluated in a preoperative setting for the evaluation of mesentery, serosal, and in any cases of contraindication of CT with contrast medium, while in the restaging clinical setting, it does not have a defined role. In the preoperative clinical setting, imaging could provide the surgeon with specific information concerning disease burden by showing the invasion of vital anatomic structures, and it is therefore essential to describe the feasibility of the surgery. However, recognizing the imaging findings of peritoneal deposits depends mainly on the histology of the primary tumor and the peritoneal spaces, thus rendering knowledge of peritoneal anatomy essential. In addition, some benign pathologies show similar imaging features that overlap with PM, making differential diagnosis difficult. It is still unclear which of the two methods, CT and MRI, is superior in terms of performance, and literature data are often controversial. Thus, the purpose of this review is to provide some practical tips for CT and MRI protocols and imaging findings essential to detect and characterize peritoneal deposits in each anatomical space, and to provide an overview of the main differential diagnosis with other peritoneal conditions. Critical relevance statement Peritoneal malignancies should be understood as a heterogeneous pattern of diseases, with variable prognosis and treatment options. CT remains the main imaging method; MRI finds application for involvement of the serosa and mesentery and when contrast-enhanced CT is not feasible. Key Points CT is the first imaging option to assess peritoneal malignancies and plan surgery; however, they have several limitations, especially in critical regions. MRI could be seen as a supporting imaging approach in a preoperative setting to study serosal, mesentery, and in case of contraindication of CT with contrast medium. Multidisciplinary approach should always be considered in the assessment of peritoneal malignancies due to their heterogeneity. Graphical Abstract